The cytotoxicity and antimicrobial activity of andrographis paniculata herbal mouthwash formulation - Alojid, Anis Amiera Muhamad (2023)
Oral disease is a global health problem caused by oral pathogens. To prevent the oral disease, mouthwash is commonly used. However, commercial mouthwash contained alcohol and other chemicals found to be toxic with unfavourable side effects. Besides, existence drugs seemed to be ineffective due to excessive use and multidrug resistance against the oral pathogens. Thus, there is a demand for a safer and effective alternative treatment in dental product. As the studies on cytotoxicity and antimicrobial activities of medicinal herb, Andrographis paniculata (AP) against oral pathogens are limited, this study proposed AP aqueous extract as herbal mouthwash to determine its effectiveness against selected oral pathogens; Porphyromonas gingivalis, Streptococcus mutans, S. sobrinus, Staphylococcus aureus, and Actinomyces viscosus. In this study, antibacterial effect of AP aqueous extract against the tested oral pathogens was determined by disc diffusion and well diffusion assays, followed by antibacterial effect of five concentrations of AP herbal mouthwash at 1000, 500, 250, 125 and 62.5 mg/mL using well diffusion and broth microdilution method. Assessment of toxicity was determined by brine shrimp lethality bioassay and 3-(4,5- dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay onto L929 fibroblast cells while the analysis of heavy metal was analysed using atomic absorption spectrometry (AAS). Stability study was carried out on the final product of AP herbal mouthwash. Results revealed that AP aqueous extract significantly inhibited the growth of all oral pathogens (p<0.05) except for S. aureus with inhibition zones ranging from 2.83 ± 0.83 mm to 14.37 ± 0.83.mm. Similar to AP aqueous extract, AP herbal mouthwash exhibited significant antibacterial activities onto all tested pathogens except for S. aureus (p<0.05) with inhibition ranging from median (IQR) of 9.50 (3.80) to median (IQR) of 15.00 (3.40). All mouthwash concentrations caused bacteria inhibition from 10.56% to 261.09% with minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) at 3.90 mg/mL to 7.81 mg/mL and 7.81 mg/mL to 62.50 mg/mL respectively. However, there was no MBC detected for S. aureus at these concentrations. Formulation of mouthwash was non-toxic to brine shrimp and L929 fibroblast cell line with LC50 value 3255.06 μg/mL and IC50 value 43.55 mg/mL respectively. AP herbal mouthwash was free from heavy metal contamination and maintained its characteristics and sterility for 12 months storage. In conclusion, AP herbal mouthwash at 7.81 mg/mL was found to be the best mouthwash formulation. However, more research works need to be carried out for its clinical use for further product commercialization.